Mining GEO and TCGA Database for Immune Microenvironment of Lung Squamous Cell Carcinoma Patients With or Without Chemotherapy - Qiang, Huiping; Li, Jiaqi; Chang, Qing; Shen, Yinchen; Qian, Jialin; Chu, Tianqing (Frontiers in Oncology, 2022)
Background: Chemotherapy is the main treatment for patients with LUSC. However, how chemotherapy affects their immune system is rarely reported. This study was aimed to compare the differences in immune microenvironment of LUSC patients with or without chemotherapy. Methods: A total of 494 LUSC samples were obtained from TCGA database. The immune cell infiltration was evaluated by ssGSEA algorithm, and the tumor subtype was assayed by ConsensusClusterPlus. The differences in tumor mutation burden (TMB), clinical information between the two types were then compared. Additionally, the differentially expressed genes (DEGs) between two types were analyzed and hub genes were validated in the GEO database. Results: LSCC samples in TCGA were divided into three subtypes. Then, combining the tumor subtype and immune scores, the samples were divided into hot and cold tumors. Regardless of whether LUSC patients received chemotherapy, the survival of the hot tumor group was not significantly prolonged compared with that of the cold tumor group. For LUSC patients who received chemotherapy, TMB value in hot tumor group was significantly higher. Total 501 DEGs were identified between two groups. The high expression of hub genes CD19, CTLA4, FCGR3B, CD80, IL-10, etc. were also validated in GSE37745 dataset. Conclusion: Chemotherapy does not affect the survival and prognosis of LUSC patients, but it significantly increases the TMB value of patients with hot tumor. The DEGs, especially hub genes, such as CD19, CTLA4, FCGR3B, etc. may serve as biomarkers to distinguish cold and hot tumors in LUSC.